Domain-specific mutations in Na[+]/K[+]-ATPase ? subunit differentially regulate sleep and circadian rhythms in Drosophila. - Chen, W.; Yu, L.; Lu, S.; Ou, M.; Chen, X.; Sun, M.; Yuan, Y.; Du, X.; Yuan, Y.; Xu, X.; Lin, Q.; Lin, Y. (Experimental Neurology, 2026)
The Na[+]/K[+]-ATPase (NKA) is a crucial membrane transporter that maintains cellular membrane potential and ion homeostasis through ATP-dependent exchange of Na[+] and K[+] ions. Its functional core is determined by the ? subunit (e.g., ATP1A1), which contains key domains including ten transmembrane segments, three well-defined intracellular regulatory regions and a simple extracellular domain. While mutations in the NKA ? subunit have been linked to sleep and circadian rhythm disorders, whether different structural domains differentially regulate these processes remains unclear. In this study, we employed CRISPR/Cas9 to generate Drosophila models carrying clinically relevant human ATP1A1 homolog (ATP?) mutations. We found that heterozygous mutations in transmembrane or intracellular actuator domains-viable only in heterozygotes-increased total sleep duration by elevating pressure to fall asleep. In contrast, homozygous intracellular domain mutations (modeling ATP?-CMT2, associated with Charcot-Marie-Tooth disease type 2) concurrently disrupted both sleep architecture and circadian locomotor rhythms, whereas heterozygous mutants showed no significant phenotypes. This reveals distinct domain-specific regulatory mechanisms for sleep and circadian rhythms by NKA ? subunit. Further, we demonstrated that NKA regulates sleep primarily through non-LNv circadian neurons, with developmental-stage-dependent effects. Conversely, its maintenance of endogenous circadian rhythms requires adult-stage functionality. These findings elucidate how domain-specific mutations differentially modulate sleep and circadian outputs, while reveling the potential neurons for NKA's regulatory roles. Our work provides new insights into the molecular genetic networks governing sleep-wake and circadian regulation.